Overload Protection and Electricity Volume Monitoring on Internet of Things (IOT)-Based Three-Phase Induction Motors - Ramly Rasyid; Miftah Muhammad; Mochammad Apriyadi Hadi Sirad (Universitas Khairun, 2024)
The protection and monitoring of the amount of electricity in three-phase induction motors that are widely used in the industry needs to be carried out continuously so that the performance of the motor continues to run well and if there is a disturbance, it can be known early. The purpose of the research to be carried out is to make a device to protect and monitor the amount of electricity of a three-phase induction motor based on the Internet of Things (IoT) and see the performance of the device. From the results of the overload protection test with the three-phase induction motor load current indicator, it can be seen that when the motor is loaded until the current rises at the R phase of 1.23 A, the S phase 1.31 A, and the T phase 1.24 A, which means that the maximum current of the induction motor is exceeded by 0.401 A as the relay works to protect the induction motor. As for the calculation of the measurement error presentation, it can be seen that for the error presentation, the voltage measurement ranges from 0.001% to 0.088%, current 0.001% to 3.509%, power factor 0.433% to 4.438%, apparent power 0.020% to 3.774%, active power 0.149% to 4.904%, and reactive power 0.008% to 4.455%. The tool that is made works well because the protection runs well and the error presentation is below 5%.